Challenges for Marine Ecological Assessments: Completeness of Findable, Accessible, Interoperable, and Reusable Biodiversity Data in European Seas - Ramírez, Francisco; Sbragaglia, Valerio; Soacha, Karen; Coll, Marta; Piera, Jaume (Frontiers in Marine Science, 2022)
The ongoing contemporary biodiversity crisis may result in much of ocean’s biodiversity to be lost or deeply modified without even being known. As the climate and anthropogenic-related impacts on marine systems accelerate, biodiversity knowledge integration is urgently required to evaluate and monitor marine ecosystems and to support suitable responses to underpin a sustainable future. The Census of Marine Life (CoML, 2000–2010) was the largest global research program on marine biodiversity. A decade after, and coinciding with the steep increase of digitalization of our society, we review existing findability, accessibility, interoperability, and reusability (FAIR) biodiversity data coming from one of the most reliable online information systems: the Global Biodiversity Information Facility (GBIF). We evaluate the completeness of available datasets with respect to the CoML benchmark, along with progresses in understanding spatial–temporal patterns of marine biodiversity in the European Seas in the last decades. Overall, we observe severe biases in available biodiversity data toward the north-western marine regions (particularly around the United Kingdom and the North Sea), the most recent years (with a peak in the number of reported occurrences in the 2010s) and the most conspicuous, abundant, and likely “appealing” taxa (e.g., crustaceans, echinoderms or fish). These biases may hamper research applications, but also global-scale data needs and integrative assessments required to support cost-effective progresses toward global biodiversity conservation. National to international joint efforts aimed at enhancing data acquisition and mobilization from poorly known regions, periods, and taxa are desirable if we aim to address these potential biases for the effective monitoring of marine ecosystems and the evaluation of ongoing impacts on biogeographic patterns and ecosystem functioning and services.